How Does Youth’s Financial Literacy Influence Their Financial Inclusion? A PLS-SEM Approach - Gaur, Pali; Tandon, Priyanka; Singh, Anurag Bhadur; Yadav, Nikhil (Indian Journal of Finance, 2025)
Purpose : The study examined the linkages between the psychology of youths toward financial literacy and their level of financial inclusion. Methodology : Fresh data were collected from 381 youths residing in the Delhi-NCR region from January 2022 to April 2022. A 5-point Likert scale questionnaire was developed using purposeful sampling, and its goodness of fit was assessed using SMART-PLS employing partial least squares-structural equation modelling (PLS-SEM). Path analysis was employed for hypothesis testing to examine the interaction of four independent variables. Findings : As per the study’s findings, financial attitude and financial behaviour were strongly related to the youth’s financial inclusion rather than financial education and awareness. The study’s conclusions clarified the investor’s psychology and enhanced financial inclusion among youths. Practical Implications : The research findings opened up additional avenues for raising young people’s financial literacy. Regulatory bodies in India should prioritize enhancing the young individuals’ understanding of finance. Despite having financial attitudes and behaviors, they had a limited grasp of finance, as seen by their limited interest in investment opportunities. This study provided valuable insights on how to improve individuals’ financial literacy. Originality : Unlike prior work on financial literacy, this study focused on the level of financial literacy among youths to understand their economic behaviour and attitudes.